Redefining awn development in rice through the breeding history of Japanese awn reduction - Suganami, Mao; Yoshida, Hideki; Yoshida, Shinya; Kawamura, Mayuko; Koketsu, Eriko; Matsuoka, Makoto; Kojima, Soichi (Frontiers in Plant Science, 2024)
The study challenges the conventional understanding of awn loss as a domestication syndrome, showing instead that many awned varieties continued to be widely grown in Japan until the early 20th century, and that selection for awn reduction was active at that time, demonstrating that awn loss is not a domestication syndrome but "a trait that emerged during crop improvement". Although selection for awnless mutants was carried out independently using different types of awned cultivars in the early 20th century in Japan, awn loss was caused by the mutation in OsEPFL1. This suggests that a single mutant haplotype of OsEPFL1 was conserved in the genomes of different cultivars and subsequently selected within each line to meet the demand for awnless varieties. The study also conducts phylogenetic analyses of EPFL1 in 48 grass plants, revealing its unique involvement in awn formation in rice, while potentially playing a different role in the domestication of other grass plants. Finally, an attempt is made to isolate an awn-forming gene that have not been identified from the awned rice cultivar “Omachi”, which is still cultivated in Japan. The results presented in this paper provide a new perspective on domestication against the conventional understanding of awn development, shedding light on its potential as a useful organ for breeding to mitigate environmental stress.